Legal Science Perspective in Modern Science Concepts - RIYADI, Padlah (Indonesia Strategic Sustainability, 2023)
Purpose - This research examines the problem of legal science, which is the center of debate among legal scholars with the problem of the perspective of Law in the concept of modern science.Methodology - This study uses empirical legal research methodology. Empirical legal research is a legal research method that uses empirical facts taken from human behavior, both verbal behaviors obtained from interviews and actual behavior carried out through direct observation. This research was conducted by examining the actual situation in society, namely looking for facts related to the problems in research.Findings - The development of the science of Law is progressing very fast along with the development of science and technology, so every law graduate must be able to adjust his knowledge to keep up with these developments. However, this has changed by leaving the original characteristics of the knowledge he studied. The science of Law is independent and should be able to work independently following pure legal concepts and produce laws following the development of more modern society.Implication - The science of Law must return to its central concept as pure legal science. The approaches used in understanding the science of Law as a modern science are by returning the science of Law to its existence as a body of knowledge that will be studied and studied accordingly.